Protocol of a scoping review of outcome domains in dermatology - Jamie J Kirkham; Amit Garg; Gregor Borut Ernst Jemec; Murad Alam; Phyllis I Spuls; John R Ingram; Jan Kottner; K Ezzedine; Umer Nadir; Areeba Ahmed; Michael D Yi; Farhana Ikmal Hisham; et al. (BMJ Open, 2024)
Introduction Core outcome sets (COSs) are agreed outcomes (domains (subdomains) and instruments) that should be measured as a minimum in clinical trials or practice in certain diseases or clinical fields. Worldwide, the number of COSs is increasing and there might be conceptual overlaps of domains (subdomains) and instruments within disciplines. The aim of this scoping review is to map and to classify all outcomes identified with COS projects relating to skin diseases.Methods and analysis We will conduct a scoping review of outcomes of skin disease-related COS initiatives to identify all concepts and their definitions. We will search PubMed, Embase and Cochrane library. The search dates will be 1 January 2010 (the point at which Core Outcome Measures in Effectiveness Trials (COMET) was established) to 1 January 2024. We will also review the COMET database and C3 website to identify parts of COSs (domains and/or instruments) that are being developed and published. This review will be supplemented by querying relevant stakeholders from COS organisations, dermatology organisations and patient organisations for additional COSs that were developed. The resulting long lists of outcomes will then be mapped into conceptually similar concepts.Ethics and dissemination This study was supported by departmental research funds from the Department of Dermatology at Northwestern University. An ethics committee review was waived since this protocol was done by staff researchers with no involvement of patient care. Conflicts of interests, if any, will be addressed by replacing participants with relevant conflicts or reassigning them. The results will be disseminated through publication in peer-reviewed journals, social media posts and promotion by COS organisations.